Synthetic Biology: Engineering Mammalian Cells To Control Cell‐to‐Cell Communication at Will - Kojima, Ryosuke; Fussenegger, Martin (ChemBioChem, 2019)
Cell‐to‐cell communication plays a key role in the regulation of many natural biological processes. Recent advances in mammalian synthetic biology are making it possible to rationally engineer cell‐to‐cell communication for therapeutic and other purposes. Here, we review state‐of‐the‐art engineering principles to control cell‐to‐cell communication, focusing on communication between mammalian cells with diffusible factors (e.g., small molecules or exosomes) or direct cell contact, and on interkingdom communication between mammalian cells and bacteria. Potential applications include construction of artificial tissues able to perform complex computations, sophisticated cell‐based cancer therapies, use of mammalian cells as a new class of cargo delivery modality, development of design principles to control pattern formation of cell populations, and treatment of infectious diseases. We also discuss the challenges facing practical applications, and possible enabling technologies to overcome them. It′s good to talk: This minireview highlights state‐of‐the‐art engineering principles for rational control of cell‐to‐cell communication, focusing on communication between mammalian cells by diffusible factors (e.g., small molecules or exosomes) or by direct cell contact, and interkingdom communication between mammalian cells and bacteria. Future biomedical applications might include therapies for various intractable diseases.